Zinc in pregnancy, associated with prolonged labor - Sare Bakouei; Fatemeh Bakouei; Fatemeh Reisian; Azita Goshtasebi (Caspian Journal of Reproductive Medicine, 2015)
Introduction: It is plausible that pregnancy may result in a decrease in the serum zinc concentration. The concentration of serum zinc is an important determinant of maternal complications. The aim of the current study was to identify serum zinc concentration and evaluate the possible correlation of this concentration with the length of first and second stage of labor in the pregnancy.